1988
DOI: 10.1104/pp.87.3.727
|View full text |Cite
|
Sign up to set email alerts
|

Sink Metabolism in Tomato Fruit

Abstract: In developing tomato (Lycopersicon esculentum Mill.) fruit, starch levels reach a peak early in development with soluble sugars (hexoses) gradually increasing in concert with starch degradation. To determine the enzymic basis of this transient partitioning of carbon to starch, the activities of key carbohydrate-metabolizing enzymes were investigated in extracts from developing fruits of three varieties (cv VF145-7879, cv LA1563, and cv UC82B), differing in final soluble sugar accumulation. Of the enzymes analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
46
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(50 citation statements)
references
References 6 publications
4
46
0
Order By: Relevance
“…Fruit growth in vitro also displays a similar growth pattern to that on intact plants (27). The in vitro cultured fruit is limited in size; however, ripening, color, and flavor are normal (24), indicating that the in vitro cultured fruit may serve as a simplified source-sink system useful as a model to study tomato sink activity.…”
Section: Discussionmentioning
confidence: 79%
“…Fruit growth in vitro also displays a similar growth pattern to that on intact plants (27). The in vitro cultured fruit is limited in size; however, ripening, color, and flavor are normal (24), indicating that the in vitro cultured fruit may serve as a simplified source-sink system useful as a model to study tomato sink activity.…”
Section: Discussionmentioning
confidence: 79%
“…Suc synthase is often associated with SUC cleavage in starch metabolism (Quick and Schaffer, 1996) (Fig. l), and its activity pattern (but not that of invertase) follows the transient starch accumulation pattern of tomato fruit (Robinson et al, 1988). SUC synthase activity has accordThis research was partially supported by grant no.…”
mentioning
confidence: 99%
“…The enzyme ADP-Glc PPase catalyzes the synthesis of ADP-Glc in starch-synthesizing tissue. Robinson et al (1988) reported that its activity, too, follows the transient starch accumulation pattern, although this loss of activity was not observed by Guan and Janes (1991). The other enzymes in the Suc-to-starch metabolic pathway during the transient starch accumulation period have not yet to our knowledge been studied, nor have their relative activities been compared.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of tomato genotypes differing in total fruit solids content showed a positive correlation between the final levels of soluble sugars and the peak levels of starch early in fruit development (Dinar and Stevens, 1981). The latter is regulated by the starch biosynthetic capacity, as determined by levels of AGP activity rather than starch degradative capacity (Robinson et al, 1988). In view of this relationship, AGP may be an attractive biotechnological target for increasing the soluble solids content of tomato fruit.…”
mentioning
confidence: 99%